Numerically investigating the effects of slip and thermal convective on nanofluid boundary layer past a stretching/shrinking surface - Najib, N.; Bachok, N.; N. Rasedee, A. F.; A. Salleh, S. N.; W. Suhaimi, W. N. (Lviv Polytechnic National University, 2023)
The study is focusing on the steady boundary layer flow, heat and mass transfer passing through stretching/shrinking sheet immersed in nanofluid in the presence of the second order slip velocity and thermal convective at the boundary. The governing partial differential equations are converted into ordinary differential equations by applying the similarity variables before being solved computationally using bvp4c function in Matlab software. The results of skin friction, heat transfer as well as mass transfer coefficient on the governing parameter such as the first order slip parameter, the second order slip parameter, Biot number, Brownian motion parameter and thermopherosis parameter are shown graphically in the discussion. The dual solutions exist in all range of stretching and shrinking parameter. Therefore the stability analysis is performed and concluded that the first solution is stable and physically relevant while the second solution acts in opposite way.